Anti-neuroinflammatory activities of lipid components from sclerotia of Lignosus rhinocerotis and stroma of Cordyceps militaris in microglia BV2 cells / Neeranjini S. Nallathamby - Neeranjini, S. Nallathamby (2017)
Inflammation in the brain, which is characterised by activation of microglia cells, plays an important role in the progression of many central nervous system (CNS) diseases. Many medicinal and edible mushrooms have been studied intensively for the treatment of neuroinflammatory conditions. In this study, an assay guided approach was adopted to identify the active ingredients of L. rhinocerotis and C. militaris responsible for its anti-neuroinflammatory activity. Preliminary in vitro antioxidant investigations of the extracts revealed that the ethanol extract of L. rhinocerotis had higher antioxidant capabilities compared to the aqueous extracts in all the three assays tested viz., DPPH, TEAC and FRAP; however, the aqueous extract of C. militaris exhibited higher antioxidant activities compared to the ethanol extract. The MTS assay revealed that both the (ethanolic and aqueous) extracts of the mushrooms did not have cytotoxic effects on the BV2 cells up to 100 μg/mL concentrations. The ethanol extracts of both mushrooms decreased NO production of LPS stimulated BV2 cells by more than 60% compared to their aqueous extracts at 100 μg/mL. Further fractionation of the ethanol extract to the hexane and ethyl acetate fractions showed that the ethyl acetate fractions of both mushrooms had a significant effect on NO production inhibition (>50%) compared to their hexane fractions at 10 μg/mL. Two bioactive subfractions, CE2 and CE3 from C. militaris and TE3 from L. rhinocerotis from the ethyl acetate fraction were obtained through vacuum liquid chromatography. These subfractions also showed more than 45% reduction in NO production at 100 μg/mL. Twenty two lipid components were identified by GCMS analysis whereby eight (8) components from TE3, eleven (11) components from CE2 and three (3) components from CE3. All these components had synergistic effect to reduce neuroinflammation. The qPCR results showed that all subfractions down regulated the proinflammatory genes (iNOS, COX2 and IL-1β) and only TE3 and CE2 up-regulated the HO-1 and NQO-1 anti-inflammatory genes. Subfractions TE3 and CE2 inhibited neuroinflammation via NRF2 and NFκB pathways while the CE3 subfraction inhibited neuroinflammation via NFκB pathway in LPS triggered BV2 cells.